Atypical Fibroxanthoma in a 13‐Year‐Old Guatemalan Girl with Xeroderma Pigmentosum. Issue 3 (4th April 2016) - Chappell, Ava G.; Chase, Elizabeth P.; Chang, Beverly; Cunningham, Eric; Mihm, Fred; Calame, Antoanella; Fudem, Gary; Cunningham, Bari
Abstract: Xeroderma pigmentosum (XP) is a rare, autosomal recessive disease involving a defect in DNA repair leading to the premature development of numerous aggressive cutaneous malignancies. Although atypical fibroxanthoma (AFX) is a neoplasm typically found in the setting of extensive sun exposure or therapeutic radiation, AFXs are rarely associated with children with XP. We report the case of a 13‐year‐old Guatemalan girl with the XP type C variant who developed one of the largest AFXs reported on a child's finger.